Feedingmarks on Dryas octopetala and Bistorta vivipara inside and otside OTCs at Finse, Norway - Birkemoe, Tone; Bergmann, Saskia; Hasle, Toril E.; Klanderud, Kari (Dryad Digital Repository, 2016)
The data is based on field observations in two summer periods. The file consists of 3 datasheets: 1. used in table 1 in publication with feeding marks on Bistorta and Dryas. Feeding index as defined in publications 2. feeding marks on other common plant species 3. precentage of each leaf removed (table 2 in publication).